The moderated effect of government regulations on the relationship between entrepreneurial orientation and competitive advantage in SMEs - Yaseen Zeebaree M.R.; Siron R.B.; Almuslamani H.A.I. (Inderscience Publishers, 2023)
This study aims to test effects of the dimensions of entrepreneurial orientation on the competitive advantage, and to investigate the moderated role of governmental regulation on the relationship between each dimensions of entrepreneurial orientation with competitive advantage in the small and medium-sized enterprises in the Kurdistan Region economy in Iraq. This study applied a quantitative approach using questionnaires as instrument tools for the collection of data. The subjects of this study were top managers working in the 3526 small and medium-sized enterprises in the Kurdistan Region. 680 questionnaires were distributed to gather data, out of which 580 useful questionnaires were selected for analysing purposes. The Structural Equation Modelling (SEM) was employed to examine the moderated role of governmental regulations on the relationship between entrepreneurial orientation and competitive advantage. The results showed that each dimension of entrepreneurial orientation is deemed to be a significant driver for competitive advantage. The results further suggested that the interaction of governmental regulations has a significant impact on the relationship between each dimension of entrepreneurial orientation and competitive advantage. Copyright 2018 Inderscience Enterprises Ltd.